Body Bias Dependence of Bias Temperature Instability (BTI) in Bulk FinFET Technology. Issue 4 (3rd January 2022) - Zhang, Jiayang; Wang, Zirui; Wang, Runsheng; Sun, Zixuan; Huang, Ru
Abstract : In this article, the body bias dependence of the bias temperature instability (BTI) in bulk FinFETs is experimentally studied, under different test conditions for the first time. In contrast to the traditional understanding that changing body bias has little impact on BTI degradation in FinFETs due to its weak body effect, it is observed that it actually has non‐negligible impacts. And a forward body bias (FBB) can reduce the BTI degradation in FinFETs, which is opposite with the trend in planar devices. The underlying physics is found due to the trade‐off between two competing factors. The results are helpful for understanding and modeling reliability in FinFETs. Abstract : It was found that two competing mechanisms lead to the difference body bias dependence bias temperature instability of between FinFET and planar devices.